Drug abuse in sports and doping (Bangladesh Medical Journal, 2014)
Drug is defined as a substance that alters the physiological processes of the body which is used for the diagnosis, prevention and treatment of disease. Abuse denotes injudicious or irrational application. The use of performance-enhancing drugs is probably the major problem facing sport today. Despite intense efforts by sporting bodies and the medical professionals to eliminate the problem, drug taking to enhance sport performance remains widespread. No player should gain an unfair advantage over other players by using an unethical substance or method. The use of drugs may also be extremely dangerous to the health of players. Drug testing programs have been established by amateur and professional sports authorities to promote a safe and fair competitive environment. Clinicians who treat athletes should be familiar with the commonly abused substances and doping methods DOI: http://dx.doi.org/10.3329/bmj.v43i1.21379 Bangladesh Med J. 2014 January; 43 (1): 46-50